Ativação da GCs no endotélio como estratégia para reverter e/ou prevenir a disfunção endotelial - Martinelli, Ariane Migliato (2019)
Introduction: The vascular endothelium presents an important protective function against cardiovascular diseases, and the release of NO has a central role in this protection. Reduction of NO bioavailability and decreased sensitivity of sGC to NO are well recognized in endothelial dysfunction. Although the underlying mechanisms of endothelial dysfunction are multifactorial, the main cause is an NO / sGC / cGMP pathway. Therefore, sGC is an important pharmacological target, which can lead to the development of key drugs in the control and treatment of hypertension, heart failure, among others. In this sense, the objective of this work was to evaluate the accumulation of cGMP in the endothelium as a strategy to revert and / or prevent endothelial dysfunction by means of the soluble guanylate cyclase activator ataciguat. Methods: Aortic rings of male Wistar rats with and without endothelium were placed in a myograph and concentration-cumulative effect curves for ataciguat were performed. In addition, intact aortic rings of normotensive (2K) and hypertensive (2K-1C) rats were incubated with ataciguat and cumulative concentration curves for acetylcholine (Ach) were measured to measure endothelial function. In addition, nitric oxide (NO) was measured by fluorescence or selective electrode on human umbilical endothelial cells (HUVECs) in response to some treatments, including ataciguat, 8-Br-cGMP and A23187. Detection of Reactive Oxygen Species (ROS) and superoxide anion (O2-) were performed using fluorescent probes, including DHE and lucigenin. Results: The presence of endothelium enhanced the ataciguat-induced relaxation in the aortic rings. In the presence of the nitric oxide synthase inhibitor (NOS), the endothelium effect was abolished. Treatment of the aortic rings with ataciguat improved the acetylcholine-induced relaxation in 2K-1C and 2K vessels. In the endothelial cell culture, treatment with ataciguat (0.1, 1 and 10 μM) decreased angiotensin II-induced superoxide anion formation. In addition, ataciguat, 8-Br-cGMP and A23187 were able to induce NO production in HUVECs. In the presence of the NOS inhibitor, the NO production induced by ataciguat and 8-Br-cGMP was abolished. Conclusion: Our results suggest that the activation of sGC in endothelial cells induces the production of NO by a mechanism dependent on the activation of NOS and decrease of O2-, with consequent potentiation of vascular relaxation dependent on the endothelium.